2018
DOI: 10.3390/en11092216
|View full text |Cite
|
Sign up to set email alerts
|

Combinatory Finite Element and Artificial Neural Network Model for Predicting Performance of Thermoelectric Generator

Abstract: Thermoelectric generators (TEGs) are rapidly becoming the mainstream technology for converting thermal energy into electrical energy. The rise in the continuous deployment of TEGs is related to advancements in materials, figure of merit, and methods for module manufacturing. However, rapid optimization techniques for TEGs have not kept pace with these advancements, which presents a challenge regarding tailoring the device architecture for varying operating conditions. Here, we address this challenge by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…In addition to that, having a deep network structure (i.e., many hidden layers) does not necessarily require any laborious feature selection and can work with raw data [29]. FE-based ANN models have been utilized for predicting stress distribution in a 3D printing process [30], bend angles in laser-guided bending [31], and performance of a thermoelectric generator [32], for example.…”
Section: Data-driven Surrogate Modelsmentioning
confidence: 99%
“…In addition to that, having a deep network structure (i.e., many hidden layers) does not necessarily require any laborious feature selection and can work with raw data [29]. FE-based ANN models have been utilized for predicting stress distribution in a 3D printing process [30], bend angles in laser-guided bending [31], and performance of a thermoelectric generator [32], for example.…”
Section: Data-driven Surrogate Modelsmentioning
confidence: 99%
“…• "Comparison of different solar-assisted air conditioning systems for Australian office buildings" with 11 citations [77]. • "Combinatory finite element and artificial neural network model for predicting performance of thermoelectric generator" with three citations [78].…”
Section: Conversion Of Thermal/electrical Energy Communitymentioning
confidence: 99%
“…The main drawback is that the heat-to-electricity conversion efficiency of thermoelectric generators (TEG) is up to 11% in laboratory environments; it is much lower in practice. In [78] they propose a model based on artificial neural networks that can predict the performance of an TEG on demand. The model evaluated predicts the performance of an EEG at 26.4 ms per data point compared to the 6.0 min required in traditional simulations.…”
Section: Conversion Of Thermal/electrical Energy Communitymentioning
confidence: 99%
“…Their results show that the employment of an appropriate ANN would be a time-effective operating method of a photovoltaic thermal hybrid system without any complex analysis and calculations; however, the scope of their study deviated from the application of ANNs to TEGs operating under various exhaust heat conditions. Kishore et al [14] suggested a finite element-ANN combined model for predicting the performance of a TEG with a high degree of accuracy. They investigated the accuracy of the ANN while varying the design parameters of a single TEM, including the length of the nand p-type thermoelectric legs, cross-sectional area of the legs, and external load resistance.…”
Section: Introductionmentioning
confidence: 99%